Cytochrome P450 2E1 aggravates DXR-induced myocardial injury through imbalanced mitochondrial OPA1 - Jiaxin Ma; Yaheng Wang; Huijiao Lv; Yu Lei; Feifei Guan; Wei Dong; He Wang; Lianfeng Zhang; Dan Lu (Cell Communication and Signaling)
Abstract Background Cytochrome P450 2E1 (CYP2E1), a drug metabolism enzyme, is linked to multiple pathophysiological states in the myocardium and may act as a sensor of heart diseases. However, the exact mechanisms of CYP2E1 in myocardial injury, particularly in chemotherapeutic agent-induced myocardial damage such as doxorubicin-induced cardiotoxicity, remain unclear. Methods Using multiple animal models of cardiomyopathy and heart failure, we observed CYP2E1 expression in myocardial mitochondria. Myocardium-specific CYP2E1 overexpression and knockout rat models were employed to study its effects on myocardial injury, assessed via echocardiography and histopathology. Mechanistic insights were derived from transcriptome analysis, mass spectrometry, co-immunoprecipitation, signal transduction analysis, and molecular biology techniques. Results CYP2E1 overexpression accelerated, while CYP2E1 knockout inhibited, myocardial injury in DXR-induced cardiomyopathy and isoprenaline-induced hypertrophic cardiomyopathy. Mechanistically, CYP2E1 was upregulated specifically in myocardial mitochondria during heart disease. This upregulation resulted in mitochondrial fragmentation and dysfunction under DXR-induced stress. CYP2E1 interacted with optic atrophy 1 (OPA1) in the inner mitochondrial membrane, leading to an imbalance between long and short OPA1 isoforms. Conclusions CYP2E1 disrupts OPA1-mediated mitochondrial dynamics, causing mitochondrial fragmentation and apoptosis, which aggravate myocardial injury. Targeting CYP2E1 may offer a therapeutic strategy to mitigate myocardial damage, particularly in chemotherapeutic drug-induced cardiotoxicity. Graphical Abstract